Energy, exergy and environmental analysis of a novel combined system producing power, water and hydrogen - Parham, Kiyan; Alimoradiyan, Hamed; Assadi, Mohsen (Pergamon-Elsevier Science Ltd, 2017)
During last years, absorption heat transformers have been used widely for boosting low-grade heat sources. In this paper, a novel multi-generation system including an open absorption heat transformer (OAHT), an organic Rankine cycle with Internal Heat Exchanger (ORC-IHE) and an electrolyzer for hydrogen production is proposed and analyzed from both first and second laws of thermodynamics and exergoenvironmental analysis points of view. To assess the cycle's performance, thermodynamic models were developed and a parametric study was carried out. The results indicate that the net power output and the hydrogen production rate will increase by boosting the inlet temperature of the waste heat using OAHT. By the growth of evaporator temperature, exergoenvironmental impact index, exergetic stability factor and exergetic sustainability index is increasing which is advantageous for the environment. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Open absorption heat transformer; Organic Rankine cycle with Internal Heat; Exchanger; Electrolyzer; Energy; Exergy; Exergoenvironmental analysis